Maori and mainstream: Towards bicultural reporting - Ian Stuart (Asia Pacific Network, 2001)
The NZ news industry—owners, management and education sectors—has long agreed that the news media requires more Maori journalists. The industry has long recognised an imbalance does exist, whatever its characterisation. But the solution is not as simple as it seems.